2022
DOI: 10.1021/acs.organomet.2c00412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Rare-Earth Metal Complexes Bearing a 2-N,N-Dimethylamino-Ethylene-Imino-Functionalized Indolyl Ligand and Their Catalytic Activities Toward Hydrosilylation of Imines

Abstract: The reactions of 2-N,N-dimethylamino-ethylene-imino-functionalized indolyl proligand 2-(Me 2 NCH 2 CH 2 N = CH)C 8 H 5 NH (HL) with [(Me 3 Si) 2 N] 3 RE(μ-Cl)Li(THF) 3 in toluene afforded a series of rare-earth metal amido complexes [κ 3 -(N,N,N)-2-(Me 2 NCH 2 CH 2 N = CH)C 8 H 5 N]RE[N(SiMe 3 ) 2 ] 2 (RE = Y (1a), Nd (1b), Sm (1c), Gd (1d), Dy (1e), Er (1f), and Yb (1g)). While the reaction of HL with [(Me 3 Si) 2 N] 3 Eu(μ-Cl)Li(THF) 3 produced the europium(II) complex in a dimeric form [{(η 5μ-η 1 :η 2), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Transition metal complexes with pincer ligands have been successfully utilized to catalyze a wide variety of transformations. Chiral pincer metal complexes are used in asymmetric catalytic reactions . Rare-earth metal pincer complexes have been demonstrated to exhibit excellent performance in the activation of small molecules like H 2 , CO, and silanes, , the catalytic conversion of unsaturated organic substrates, the and regioselective and stereoselective catalytic polymerization of conjugated dienes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal complexes with pincer ligands have been successfully utilized to catalyze a wide variety of transformations. Chiral pincer metal complexes are used in asymmetric catalytic reactions . Rare-earth metal pincer complexes have been demonstrated to exhibit excellent performance in the activation of small molecules like H 2 , CO, and silanes, , the catalytic conversion of unsaturated organic substrates, the and regioselective and stereoselective catalytic polymerization of conjugated dienes …”
Section: Introductionmentioning
confidence: 99%
“…Based on the multicoordination modes and nonsymmetric motif of the indolyl skeleton and the easy regulation of the pincer ligands, different NCN, NCO, and NCC pincer proligands (Scheme ) and corresponding complexes were designed and synthesized. These complexes showed excellent catalytic performance in olefin polymerization, c hydroboration of nitriles, a and hydrosilylation of imines. c Recently, it was found that 1,3-functionalized indole can form the indol-2-yl-based NCN pincer rare-earth complexes, which exhibited excellent activity toward the hydrosilylation of terminal olefins; however, the reactivity of the nonsymmetric pincer rare-earth metal complexes toward organic compounds has received less attention. Thus, a series of pincer rare-earth metal dialkyl complexes bearing 1,3-functionality indolyl skeletons were synthesized, and their reactivity toward various organic compounds and o -carborane has been explored with the disclosure of various reactivity patterns, such as sp 2 C–H bond activation, σ -bond metathesis, migration insertion, and homolytic redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Various procedures have been developed for the hydrosilylation of different functional groups such as alkene, ,, alkyne, ,, imine, carbonyls, and carboxylic derivatives. Additionally, there are numerous reports on catalytic double hydrosilylation of nitriles to 1,1-disilylamines. ,, However, partial mono-hydrosilylation of nitriles to N-silyl aldimines remains a significant challenge. Due to N-silylimines being much more reactive than nitriles, these are further reduced to give the disilylamine products. ,, In addition, N-silylimines are very unstable . These N-silylated imines are suitable precursors in medicinal chemistry, nitrogen-containing organic compounds, and silicon-containing polymers. , N-silylimines are key intermediates for further functionalization .…”
Section: Introductionmentioning
confidence: 99%